Lose Your Mother: A Journey Along the Atlantic Slave Route - Hartman, Saidiya (Serpent's Tail, 2021)
The slave, Saidiya Hartman observes, is a stranger torn from family, home, and country. To lose your mother is to be severed from your kin, to forget your past, and to inhabit the world as an outsider. In Lose Your Mother, Hartman traces the history of the Atlantic slave trade by recounting a journey she took along a slave route in Ghana. There are no known survivors of Hartman's lineage, no relatives to find. She is a stranger in search of strangers, and this fact leads her into intimate engagements with the people she encounters along the way, and with figures from the past, vividly dramatising the effects of slavery on three centuries of African and American history.
English
Keywords: HN1-995 Social history and conditions; Slavery